Analisis Strategi Bisnis PT United Tractors Tbk (UNTR) dalam Menghadapi Dinamika Industri Pertambangan dan Alat Berat dengan Pendekatan Manajemen Stratejik - Harda Grahita (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the strategic position of PT United Tractors Tbk (UNTR) and to formulate optimal business strategies amid the increasingly complex dynamics of the mining and heavy equipment industries. The research employs a descriptive qualitative approach with a case study design, utilizing secondary data from annual reports, financial statements, and corporate strategic documents. A comprehensive analysis was conducted using strategic management frameworks including PESTEL analysis, Porter's Five Forces, EFE Matrix, IFE Matrix, Competitive Profile Matrix, TOWS Matrix, SPACE Matrix, BCG Matrix, IE Matrix, and Quantitative Strategic Planning Matrix (QSPM). The findings indicate that UNTR is positioned in the Grow and Build quadrant with an aggressive strategic orientation. The QSPM analysis recommends a Product Development strategy with the highest Total Attractiveness Score (TAS) of 6.88 as the priority strategic alternative, supported by diversification strategies into nickel, gold, and renewable energy sectors. This study concludes that UNTR's success in maintaining sustainable growth critically depends on the company's ability to execute its 3D strategy (Differentiation, Diversification, Digitalization) and 3P roadmap (Portfolio, People, Public Contribution) synergistically